Strategi Promosi Pariwisata Di Dinas Pariwisata Provinsi Nusa Tenggara Barat (Studi Kasus Promosi Pariwisata Pasca Gempa Bumi di Pulau Lombok Tahun 2018) - Mar diah; Rishan Adha; Kur niawan (Universitas Muhammadiyah Mataram, 2019)
This study aims to find out how tourism promotion strategies and inhibiting factors for tourism promotion in the NTB Province Tourism Office after the earthquake earth on the island of Lombok in 2018. The method used in this study is a descriptive qualitative method with speakers from NTB Province Tourism Office employees. Technical data were collected by observation, interview, and documentation techniques. Technical data analysis used includes data collection, data reduction, data presentation and then drawing conclusions. The results of the study show that the tourism promotion strategy at the NTB Province Tourism Office uses strategies through the promotion mix, namely advertising, personal sales, public relations and direct marketing. Factors inhibiting tourism promotion at the NTB Province Tourism Office consist of internal factors and external factors.